In the following figure, if AC = BD, then prove that AB = CD.
From the figure, it can be observed that
AC = AB + BC
BD = BC + CD
It is given that AC = BD
AB + BC = BC + CD ......(1)
According to Euclid’s axiom, when equals are subtracted from equals, the remainders are also equal.
Subtracting BC from equation (1), we obtain
AB + BC − BC = BC + CD − BC
AB = CD
Concept: Euclid’S Definitions, Axioms and Postulates
Is there an error in this question or solution?
Video TutorialsVIEW ALL 
Video Tutorials For All Subjects
- Euclid’S Definitions, Axioms and Postulates